Factores intrínsecos y extrínsecos asociados a flebitis en pacientes hospitalizados - Joaquin-Apaza, Abigail (2021)
Nursing care in central and peripheral venous access is part of nursing work, and the quality of care is affected by the presence of phlebitis in various hospitalization areas. Therefore, factors related to phlebitis are identified. Objective: To analyze the development of scientific evidence on intrinsic and extrinsic factors associated with phlebitis in hospitalized patients. Methodology: A literature search was carried out in databases over the last ten years. There was no language restriction, studies in English, Spanish and Portuguese published in full-text indexed journals were included. A critical analysis of each selected article was carried out, creating a matrix for ordering and categorizing. Results: From a total of 64 articles, 9 were included of which 2 were English and 7 in Portuguese, whose results were that there are intrinsic factors specific to the patient, extrinsic factors that correspond to factors that can be avoidable by the nursing professional when identified. Conclusions: Phlebitis is considered an indicator of nursing service quality. In the course of the article reviews, multiple factors related to phlebitis have been identified, with which preventive, corrective and educational measures should be taken in the areas where venous accesses are manipulated, avoiding future complications, as well as improving the quality of care reflected in the indicators of phlebitis with a zero result as a goal.